Sunday

April 20, 2014

April 20, 2014

Posted by **Margie...** on Saturday, December 2, 2006 at 6:53pm.

1. 3x - 7 = -4

2. 3x - 7 + 7 = -4 + 7

3. 3x + 0 = -4 + 7

4. 3x + 0 = 3

5. 3x = 3

6. (1/3) 3x = 3 (1/3)

7. (1/3) 3x = 1

8. 1x = 1

9. x = 1

Is this problem about explaining each step?

yeah like you have to write the property of each

Are you going to help?PLease do!

Hmmm, I don't know if I can do it in the way you are supposed to do it.

I think you are asked to just write down what ahppens in each step. E.g.

-7 + 7 = 0, because 7 is the inverse w.r.t. addition to 7.

In another step it is used that 3x + 0 = 3x. Here you use the definition of the zero element. that x + 0 = x for all x.

in another you see that 1/3*3*x = 1*x is used. Here you use that:

a*b*c = (a*b)*c

and that

1/3 is the inverse w.r.t. multiplication of 3.

and in another step you see that

1*x = x is used.

here the property of the unit element is used. 1*x = x because 1 is the unit element w.r.t. multiplication.

That is how you do it but can you help me then?

I think you can just use use what I wrote. There is nothing more to this problem than using the definitions of minus a number and 1/number as the inverses w.r.t. addition and multiplication and the unit elements 0 for addition and 1 for multiplication.

so can you write the answers next to the numbers

ex.1.dfgb

2.sdfhvn

PLZ and thanks

Ok, I'm not sure you are suppose to do it like this:

1. 3x - 7 = -4

Add 7 to both sides (+7 is the inverse of -7 w.r.t. addition, this wil yield zero and zero added to 3x will leave the 3x invariant):

2. 3x - 7 + 7 = -4 + 7

Now we use that -7 + 7 = 0:

3. 3x + 0 = -4 + 7

Next step is -4 + 7 = 3

4. 3x + 0 = 3

Here we use that 0 is the unit lelemnt w.r.t. addition.

5. 3x = 3

Next we multiply both sides by 1/3:

6. (1/3) 3x = 3 (1/3)

1/3 is the inverse w.r.t. multiplication of 3. we use this on the right hand side:

7. (1/3) 3x = 1

And again in the left hand side.

8. 1x = 1

1*x = x, becuase 1 is the unit w.r.t. multiplication:

9. x = 1

**Related Questions**

PRoof reasons in Algebra - Statements Reasons 1. 3x - 7 = -4 1. 2. 3x - 7 + 7...

Reasons in Proof - *I KNow only #6 which is relfexive,I think...You have to find...

Algebra - (3x+4)/(3x-4)+(3x-4)/(3x+4) --------------------------- Divide top by ...

calculus - I am trying to find equation of the tangent line to the curve 2/(1-3x...

algebra - Could you please check my answer to this problem: Simplify the ...

one more elgebra problem... - which equation represents a line parallel to the ...

BobPursley..here it is: - Problem 1: (x-2)/(3x+4) - 6x/(x+1) What I did: Common ...

Calculus (Help) - Also I would like to know how to set this problem up in ...

algebra functions - can someone please check my answer For each problem, ...

Algebra.. - Check These Answers Please? f(x)= x^2+3 ; g(x)=3x-1 1. (f+g) =x^2+3x...